2017
DOI: 10.1002/jocb.219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Creativity Through the Degrees of Solidity of Its Assessment: A Relational Approach

Abstract: In this paper, we introduce a new approach to creativity assessment. Arguably, one of the main obstacles to creativity assessment is that creativity criteria are likely to change depending on what is assessed and who is making the assessment. We argue that we might be able to solve this problem by adopting a relational ontology, i.e., an ontology according to which beings of the world acquire their properties by relating to other beings. First, we present the main consequences of this ontological approach for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The more that different ideas conflict or point in alternative directions, the more controversial work on and with them will be and the harder they might be to translate and align (Callon, 2008;van Werven, Bouwmeester, & Cornelissen, 2019). This is the case, whether we think of the focusing of organizational attention in order to achieve some desired premises as a prelude to the generation of ideas (Martine, Cooren, & Bartels, 2017); the selection and pursuit of some ideas over others as they emerge (Harrison & Rouse, 2015); the tensions between new ideas and existing practices and routines (Välikangas & Gibbert, 2015), or the contestation for future prioritization of resources committed to the maturation and realization of ideas-in-the-making (Coldevin, Carlsen, Clegg, Pitsis, & Antonacopoulou, 2019). Yet, the generative use of conflicts and the productive use of power in creativity is largely uncharted in organization studies.…”
Section: Introductionmentioning
confidence: 99%
“…The more that different ideas conflict or point in alternative directions, the more controversial work on and with them will be and the harder they might be to translate and align (Callon, 2008;van Werven, Bouwmeester, & Cornelissen, 2019). This is the case, whether we think of the focusing of organizational attention in order to achieve some desired premises as a prelude to the generation of ideas (Martine, Cooren, & Bartels, 2017); the selection and pursuit of some ideas over others as they emerge (Harrison & Rouse, 2015); the tensions between new ideas and existing practices and routines (Välikangas & Gibbert, 2015), or the contestation for future prioritization of resources committed to the maturation and realization of ideas-in-the-making (Coldevin, Carlsen, Clegg, Pitsis, & Antonacopoulou, 2019). Yet, the generative use of conflicts and the productive use of power in creativity is largely uncharted in organization studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although conducting the latter in future studies would be useful, the goal of this exploratory research was to gain a first insight into how textual and human actors make differences in situations by carrying or conveying what other actors are saying, doing, thinking, and feeling, and through their vector effects, contribute to the composition of the nature of relations. Hence, the method we used to analyze our data parallels the method other scholars have used in studies of communicative relationality (see Cooren, 2018a ; Cooren et al, 2017 ; Kuhn et al, 2017 ; Martine et al, 2019 ).…”
Section: Methodsmentioning
confidence: 95%
“…Both of them have found that distant temporal distance had a beneficial effect on creative thinking (Förster et al, 2004;Chiu, 2012). However, in the area of creativity research, there exists a common dilemma -a disparity in creativity measurement methods often produces dissimilar results (Hennessey and Amabile, 2010;Martine et al, 2017). Thus, to improve the validity of the result regarding the effect of distant temporal distance on creative thinking, the present study sought to test this effect by using more different types of creative thinking measurement tools.…”
Section: Distant Temporal Distance and Creative Thinkingmentioning
confidence: 96%